Police Digital Narrative in the Transformation Era: Netnographic Analysis of Instagram ADS Using NVIVO - Albert Christoper; Ovalia Rukmana (Eduvest - Journal of Universal Studies, 2025)
The digital transformation era has revolutionized how public institutions, including the police, interact with society. Amid rising demands for transparency and two-way communication, social media platforms like Instagram have become strategic channels for delivering educational messages and reinforcing institutional legitimacy. However, systematic studies on how police narratives are constructed and disseminated in digital spaces remain limited. This research aims to analyze the digital communication strategies of the police on Instagram, identify dominant keywords, and map thematic clusters using a netnographic approach supported by NVivo 15 software. Primary data included Instagram Ads content, captions, and reels from official police accounts, while secondary data comprised academic literature and institutional reports. Methods involved digital documentation, word frequency analysis, and cluster visualization. Findings revealed that police narratives emphasize operational duties (e.g., patrol, coordination), public service, and professional image-building, with keywords like protection and violation appearing frequently. Cluster analysis highlighted the alignment between institutional functions and communication strategies. The study concludes that NVivo enhances the validity of netnographic research, offering insights into the dynamics of institutional digital communication. Practical implications include recommendations for data-driven communication strategies for public institutions, while theoretical contributions expand the literature on digital netnography and police-public engagement.